Analisis Usaha Pengeringan Umbi Porang di PT. Hai Makmur Indonesia Kelurahan Kauman Kecamatan Srengat Kab. Blitar Jawa Timur - Achmad Sandy Irawan (Syntax Corporation Indonesia, 2024)
This research was conducted in February - June 2023 at PT. HAI MAKMUR INDONESIA in Kauman Village, Srengat District, Blitar Regency, East Java. This study aims to: (1) Find out how to dry porang chips at PT. Hai Makmur Indonesia, Kauman Village, Srengat District, Blitar Regency (2) Find out the production costs of the porang chip drying business at PT. Hai Makmur Indonesia, Kauman Village, Srengat District, Blitar Regency, (3) For the owner, the results of this study are expected to be used as consideration and input in business development For the owner, the results of this study are expected to be used as consideration and input in business development of PT. Hai Makmur Indonesia. The research method used in this study is a quantitative descriptive method. The descriptive method is defined as research that intends to present data by analyzing the data obtained so as to obtain a clear picture. The quantitative descriptive method is a method that emphasizes the objective measurement aspect of social phenomena, quantitative research is processed and analyzed using statistics. The results of the study indicate that the production process carried out in the porang drying business in Kauman Village, when viewed from the nature of the production process, is a synthetic type of production because it undergoes physical or chemical changes, namely changes in porang tubers into porang chips. The results of the sensitivity analysis of net benefits and operational maintenance indicate that this business is still safe if there are changes in the factors that influence it.